Conceptual parameters of the creative economy and its categorical outline - Khussainova, Zh.S.; Assanova, M.K.; Bektleyeva, D.Ye.; Abauova, G.M.; Kankulov, M.K. (BUKETOV BUSINESS REVIEW, 2022)
Object: Шdentification of the nature of the creative economy and the area of its categorical structure based on a review of existing research in this subject area with the identification of dominant trends and rapper guidelines. Methods: An arsenal of systemic, structural and comparative methods of analysis, VOSviewer software, bibliometric methods and visualization. Results: The parameters of the current level of scientific interest in the development of the creative economy are determined; the genesis of research on the concept of the creative economy is revealed; the scientific map, categorical outline and conceptual structure of thematic clusters in the field of creative economy research are systematized; priority and current trends of promising research in the field of conceptualization of the creative economy are determined. Conclusions: The study results indicate an ever-growing scientific interest in the problems of the creative economy and creative industries. Creative industries are not a direct substitute alternative to the basic industrial sectors of the domestic economy. They make an additional contribution to the overall results of inclusive development and form its distinctive market patterns, specific benefits and specific clusters. Thus, the issues of the formation of the creative economy, creative industries, market mechanisms for their assessment, including in the coordinates of the inclusion of all social groups, and their implementation in the state economic policy in domestic conditions are being updated. There is also an urgent need to develop tools aimed at expanding the boundaries of creative clusters for applied illustration of their effectiveness and real competitiveness in the domestic environment.